2014
DOI: 10.1038/nn.3675
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cellular node for motor control pathways

Abstract: The rich behavioral repertoire of animals is encoded in the CNS as a set of motorneuron activation patterns, also called ‘motor synergies’. However, the neurons that orchestrate these motor programs as well as their cellular properties and connectivity are poorly understood. Here we identify a population of molecularly defined motor synergy encoder (MSE) neurons in the mouse spinal cord that may represent a central node in neural pathways for voluntary and reflexive movement. This population receives direct in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
206
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(228 citation statements)
references
References 52 publications
15
206
0
Order By: Relevance
“…Optical stimulation of ventral glutamatergic neurons at L2 evokes flexor and at L5 extensor bursts (Hägglund et al 2013). Individual motoneuron pools are monosynaptic targets of a premotor column in medial lamina V, believed to encode synergies, with evidence for a rostrocaudal topography (Levine et al 2014). …”
Section: Topography Of Synergiesmentioning
confidence: 99%
“…Optical stimulation of ventral glutamatergic neurons at L2 evokes flexor and at L5 extensor bursts (Hägglund et al 2013). Individual motoneuron pools are monosynaptic targets of a premotor column in medial lamina V, believed to encode synergies, with evidence for a rostrocaudal topography (Levine et al 2014). …”
Section: Topography Of Synergiesmentioning
confidence: 99%
“…However, there remains heated debate regarding whether these observations reflect a neurophysiological basis or are an epiphenomenon of task constraints and biomechanics (6)(7)(8). This controversy stems from a lack of direct evidence for (or against) the neural implementations of muscle synergies in the CNS (9)(10)(11). Previous studies have suggested that output projections of spinal premotor interneurons (PreM-INs) to motoneuron pools are the neural basis of coordinated muscle activity (10,11).…”
mentioning
confidence: 99%
“…This controversy stems from a lack of direct evidence for (or against) the neural implementations of muscle synergies in the CNS (9)(10)(11). Previous studies have suggested that output projections of spinal premotor interneurons (PreM-INs) to motoneuron pools are the neural basis of coordinated muscle activity (10,11). For example, Hart and Giszter demonstrated in spinalized frogs that PreM-INs have divergent output projections to motoneurons that match the pattern of muscle synergies extracted during spinal motor behaviors (e.g., wiping reflexes) (10).…”
mentioning
confidence: 99%
“…Samuel Pfaff (Salk Institute, La Jolla, USA) described the motor circuitry that coordinates common movement patterns, i.e. the motor synergy encoder (MSE), which is defined by the presence of the transcription factors Tcafp2β and Satb1/2 (Levine et al, 2014). The MSE interneurons coordinate distal and proximal limb MNs.…”
Section: Assembly Of Functional Circuitsmentioning
confidence: 99%